CHEMICAL CHARACTERIZATION OF LIGNANS FROM ARAUCARIA ARAUCANA A NATIVE CONIFER OF CHILE AND EVALUATION OF THEIR CYTOTOXICITY AND ANTIOXIDANT ACTIVITIES - Gaston Bravo; Solange Torres; Fabian Figueroa; Claudia Perez; Cristian Paz; Giovanni Turchetti; Antonio Tiezzi; Jose Becerra (Journal of the Chilean Chemical Society, 2020)
Araucaria araucana is a native conifer of Chile commonly called Araucaria. The knots of Araucaria are extremely hard wood and highly rot-resistant, they can be found in the forest decades after that the tree has dead and decomposed. Here we report the phytochemical characterization of different parts of the Araucaria as stemwood, branch and knots, founding a remarkable difference in the content of extractables in these parts, as well as the lignan composition, which is higher in knots than in branches or stemwood. Eudesmin was isolated and crystallized from organic extract of knots, its structure was determinate by NMR; moreover, secoisolariciresinol, lariciresinol and matairesinol were identified by GCMS and HPLC in contrast to standards, and quantified in stemwood, branch and knots. The results showed that secoisolariciresinol is the main lignan with 45.77 mg g-1, followed by eudesmin with 22.68 mg g-1, lariciresinol 4.57 mg g-1 and matairesinol with 1.19 mg g-1. The antioxidant activity in terms of DPPH assay showed that knotwood extract displays the higher activity, meanwhile that eudesmin did not displays activity in DPPH assay. The cytotoxic activity against SHSY5Y neuroblastoma and P3X myeloma cell lines, revelated a moderate activity of extracts, while eudesmin did not showed activity.